Managing logistics and transportation in the public sector - Matthews, Darin; Stanley, Linda L. (London : Routledge, 2022)
Managing Logistics and Transportation in the Public Sector, Second Edition thoroughly examines the world of transportation as it relates to public procurement, stressing the importance of not only procuring the right goods, materials, and services, but also ensuring their proper deliveryto their final destination. Designed to educate the public procurement professional on ways to realize enhanced cost savings, it offers an introduction to the history of transportation, as well as industry terminology and accepted practices. Authors Darin Matthews and Linda Stanley explore recent transportation industry evolutions, including the development of important technologies like package tracing, delivery notification, and drone delivery, and ways to successfully integrate this technology. Sustainability in transportation--including product packaging, material reuse, and reduced emissions for delivery vehicles-- islikewise examined. Through the use of case studies and transportation industry resources, Managing Logistics and Transportation in the Public Sector, Second Edition offers a complete package for professionals looking to enhance their knowledge of logistics and transportation, as well as for university courses on transportation, supply chain management, and public procurement.
1. Overview of Logistics and Transportation 2. Transportation Law 3. Mode and Carrier Selection 4. Costs of Transportation 5. The Transportation Contract 6. Global Transportation 7. Technology in the Supply Chain 8. Sustainability in Transportation
Keywords: Business logistics; Government purchasing; Physical distribution of goods; POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Public Policy / General